Childhood peer status and circulatory disease in adulthood: a prospective cohort study in Stockholm, Sweden. Issue 9 (15th September 2020) - Miething, Alexander; Almquist, Ylva Brännström
Abstract : Objectives: Childhood conditions have been recognised as important predictors of short-term and long-term health outcomes, but few studies have considered status position in the peer group as a possible determinant of adult health. Lower peer status, which often reflects experiences of marginalisation and rejection by peers, may impose inequality experiences and leave long-lasting imprints on health. The present study aimed to examine whether peer status is associated with the risk for circulatory disease in adulthood. Design: Prospective cohort study based on the Stockholm Birth Cohort Multigenerational Study (SBC Multigen). Setting: Stockholm metropolitan area. Participants: All individuals who were born in 1953 and resident in the greater metropolitan area of Stockholm in 1963 (n=14 608). The analytical sample consisted of 5410 males and 5990 females. Peer status was sociometrically assessed in cohort members at age 13. The survey material was linked to inpatient care registers that contained information about circulatory diseases (n=1668) across ages 20–63. Cox proportional hazard models were used for the analysis. Outcome measure: Circulatory disease. Results: Peer marginalisation at age 13 resulted in significantly higher risks of circulatory disease in adulthood among males (HR 1.34; 95% CI 1.09 to 1.64) and females (HR 1.33; 95% CI 1.04 to 1.70) alike. A graded relationship between peer status and circulatory diseases was detected in females (p=0.023). Among males there was a threshold effect, showing that only those in the lowest status position had significantly increased risks of circulatory disease. The associations remained significant after adjusting for various conditions in childhood and adulthood. Conclusions: This study shows that circulatory diseases in adulthood may be traceable to low peer status and marginalisation in childhood. It is suggested that peer status in late childhood may precede social integration in adolescence and adulthood, acting as a long-term stressor that contributes to circulatory disease through biological, behavioural and psychosocial pathways.